Environmentally benign catalytic hydroformylation-oxidation route for naproxen synthesis - Rajurkar, Kalpendra B.; Tonde, Sunil S.; Didgikar, Mahesh R.; Joshi, Sunil S.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2007)
Hydroformylation of 6-methoxy-2-vinylnaphthalene (MVN), using homogeneous Rh(CO)acac) as a catalyst and a chelating bidentate ligand (1,2-bis-(diphenylphosphino) ethane, dppe), followed by oxidation of the product (2-(6-methoxynaphthyl) propanal, 2-MNP) has been studied as an alternative route for the synthesis Of D,L-naproxen. The feasibility of the MVN hydroformylation route has been demonstrated, and a detailed study has been reported on the key hydroformylation step. The roles of the catalyst, ligands, and solvents, as well as the effect of reaction conditions on the reaction rate and regioselectivity of the product 2-MNP, have been investigated. With Rh(CO)2(acac) as a catalyst and dppe as a ligand, > 98% selectivity to 2-MNP (an important precursor to D,L-naproxen) has been achieved. A possible mechanism to explain the variation in regioselectivity with Rh(CO)(2)(acac) as a catalyst and dppe as a ligand has been discussed. The kinetics of the hydroformylation step has been investigated and a rate equation has been proposed. The second step in the proposed route for naproxen-the oxidation of 2-MNP to 2-(6-methoxynaphthyl) propanoic acid (2-MNPA, or naproxen) - has been studied using Na2WO4 as a catalyst and tetrabutyl ammonium hydrogen sulfate (TBAHS) as the phase-transfer catalyst with H2O2 as the oxidant for the first time. Screening of the catalysts that consisted of the early transition metals, such as salts of tungsten, vanadium, and molybdenum showed that Na2WO4 gives the best performance for the oxidation step with > 80% selectivity to 2-(6-methoxynaphthyl)propanoic acid (2-MNPA/naproxen). This study would be valuable in developing a new environmentally benign route for naproxen synthesis.
Joint 6th International Symposium on Catalysis in Multiphase Reactors/5th International Symposium on Multifunctional Reactors (CAMURE-6/ISMR-5-), Pune, INDIA, JAN 14-17, 2007